The drunken woman in the art of Jan Steen, Dutch Baroque painter, an Ovidian image? (Minerva, 2020)
The author of this article suggests the possible relation between the frequent motif of the drunken woman in the art of the Dutch Baroque painter Jan Steen (1626-1679) and a fragment from Ovid’s poetry (ars 3,761-768), where the Roman elegiac poet criticises this kind of behaviour in women.
Keywords: Ovid; Jan Steen; woman; drunkenness; Roman elegy; Dutch Baroque painting